Analysis and Dynamic Routing Implementation of Hierarcical Healthcare Referral System - Khairurizal Alfathdyanto; Abdullah Alkaff; Nurlita Gamayanti (Department of Electrical Engineering ITS and FORTEI, 2017)
Hierarchical Healthcare Referral System (HHRS) is implemented by National Insurance Providing Agency (BPJS) as part of the healthcare insurance policies. Patients who want to get health insurance in a hospital should get a referral from the community health center in which they are registered. Congestion of patients happens in certain hospital as there is no policy implemented to govern the referral system. In this paper, HHRS is modeled as a network of queuing system and is analyzed for its queue performances. Analysis of queuing network performances shows the influence patient preferences to buildup congestion of patients in hospitals. Referral is then controlled by means of dynamic routing with considering patient preferences. Estimation of arrival rate is done with hypercube queuing theory which concerns user preference. Simulation shows that patient preferences affect the arrival rate at each hospital, the application of dynamic routing can reduce the maximum utility and reduce the average waiting time, prioritization of patients improve dynamic routing performance on systems with a high workload.Keywords: dynamic routing; hierarchical healthcare referral system; patient priority; queueing networks;